2013 World Electric Vehicle Symposium and Exhibition (EVS27) 2013
DOI: 10.1109/evs.2013.6914892
|View full text |Cite
|
Sign up to set email alerts
|

GPS measurement of Swedish car movements for assessment of possible electrification

Abstract: To enhance the transition to electrified vehicles, such as PHEVs, the use patterns of cars need to be well understood and thus information about individual vehicle's movements over longer time periods is needed. This is of major importance for instance for optimal powertrain and battery design, estimation of consumer viability and potential for PHEVs and for assessment of policies for shifting energy use in transport sector from fuel to electricity. Good and publicly available data of this kind is today unfort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…The driving should therefore be reasonably representative for Swedish movement patterns among cars. (The data set for movement patterns has been previously described, when not fully completed though, in [11] and is also presented in parallel at this conference [12]). We assume a so called charge depleting/charge sustaining mode (CD/CS-mode) for the PHEV, that is, the car is first driven on electricity only and when the battery reaches its lowest allowed state of charge (SOC), it will sustain the long term SOC and functions as a hybrid until next recharging.…”
Section: Methodsmentioning
confidence: 99%
“…The driving should therefore be reasonably representative for Swedish movement patterns among cars. (The data set for movement patterns has been previously described, when not fully completed though, in [11] and is also presented in parallel at this conference [12]). We assume a so called charge depleting/charge sustaining mode (CD/CS-mode) for the PHEV, that is, the car is first driven on electricity only and when the battery reaches its lowest allowed state of charge (SOC), it will sustain the long term SOC and functions as a hybrid until next recharging.…”
Section: Methodsmentioning
confidence: 99%
“…EVs are implemented in the ENODE model using individual driving patterns. Travelling patterns from a measurement campaign performed in the region of Västra Götaland (western part of Sweden) are applied, consisting of the GPS data obtained from about 770 randomly chosen gasoline-and diesel-driven vehicles that completed 107 910 trips in the period of 2010-2012 [23,44]. The vehicles GPS-equipped, which were randomly selected from the Swedish vehicle database, are representative of Sweden in terms of a number of parameters (e.g.…”
Section: Ev Driving Patternsmentioning
confidence: 99%
“…An individual EV owner can only store about 15-85 kWh in their battery, whereas on an aggregated scale, EV batteries can provide substantial amounts of battery capacity and energy storage capacity for the system. The analysis of passenger vehicle driving patterns performed by Karlsson and Kullingsjö [23] has shown that even with relatively small EV battery capacities, a large part of the passenger EV fleet does not require battery recharging every day in order to manage the daily driving demand, as this part of the car fleet is typically parked for about 95% of the time [23]. It is, therefore, of interest to investigate EVs as a variation management strategy for both solar and wind power using real vehicle driving data.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden individual multiday movement patterns have been logged by GPS for a number of privately driven conventional cars constituting a representative sample of Swedish driving [39,40]. The aim of this study is to use this database to explore how individual movement patterns, under various charging infrastructure and a wide range of techno-economic conditions, affect the PHEVs' optimal battery size, economic viability and potential to increase the electrification of Swedish driving.…”
Section: Introductionmentioning
confidence: 99%